(untitled) (قضايا سياسية, 2024)
Abstract; The research examined the role of the League of Arab States in confronting the crises and conflicts that some Arab countries faced after 2011, to demonstrate the extent of its effectiveness in performing its duties towards member states, by identifying the circumstances of its founding and its most important objectives, and its position on the Arab crises during the study period, and then evaluating its performance in Managing these crises. The study concluded that the League was weak and ineffective in managing the situation towards the Arab member states, and that it had become a subordinate entity that fulfilled the interests of some countries and regional and international powers.